Bezier curves method for fourth-order integrodifferential equations - Ghomanjani, Fateme; Kamyad, Ali Vahidian; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
The Bezier curves method is applied to solve both linear and nonlinear BVPs for fourth-order integrodifferential equations. Also, the presented method is developed for solving BVPs which arise from the problems in calculus of variation. These BVPs result from the Euler-Lagrange equations which are the necessary conditions of the extremums of problems in calculus of variation. Some numerical examples demonstrate the validity and applicability of the technique.